Analisis Layanan Google Scholar Sebagai Bahan Referensi Terhadap Kepuasan Mahasiswa - T. Husain (ULTIMA InfoSys, 2019)
This study aim to determine the factors that influence Google Scholar services on college students use the IS Success Model. There are five developed constructs of Technology Acceptance Model consist of network externality, information quality, system quality, service quality and satisfaction. The study is causality using survey approach. The amount of respondents sample is 224 respondents from STMIK Widuri college students. The method of data analysis uses path analysis with sobet tests. The results of this research showed that: (1) network externality have a positive direct effect on the each construct of the IS Success Model is information quality, system quality and service quality; (2) merely system quality has a positive direct effect on the satisfaction college students; and (3) in addition, merely network externality also has a positive indirect effect on the satisfaction college students through system quality.